1989
DOI: 10.1016/0014-5793(89)80200-5
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species induce antigenic changes in DNA

Abstract: Reactive oxygen species (ROS) are released at sites of inflammation during the respiratory burst which accompanies the phagocytic process. Using an in vitro system to simulate this process we have shown that ROS induce antigenic changes in DNA. More specifically, results of experiments using ROS scavengers have shown that hydroxyl radicals produced in close proximity to DNA-bound metal ions play a predominant role. ROS-mediated attack resulted in increased binding of anti-DNA antibodies to the denatured DNA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…In particular, ROS modification of both IgG [29] and DNA [30] can render these macromolecules more susceptible to forming interactions with circulating autoantibodies in RA and SLE, respectively, thus promoting immune complex formation, which may be important in their pathogenesis. The results of 80HDG detection in urine and immune complex-derived DNA of SLE and RA patients showed that whilst both disease states had similar inflammatory components, as determined by standard serological markers of inflammatory activity, the patterns of DNA damage were very different.…”
Section: D~cu~ionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, ROS modification of both IgG [29] and DNA [30] can render these macromolecules more susceptible to forming interactions with circulating autoantibodies in RA and SLE, respectively, thus promoting immune complex formation, which may be important in their pathogenesis. The results of 80HDG detection in urine and immune complex-derived DNA of SLE and RA patients showed that whilst both disease states had similar inflammatory components, as determined by standard serological markers of inflammatory activity, the patterns of DNA damage were very different.…”
Section: D~cu~ionmentioning
confidence: 99%
“…It remains to be clarified whether or not cells from SLE patients have an inherent deficiency in the repair of 80HDG, and whether this is a phenomenon peculiar to lymphocytes or common to all cell types in SLE, but the observation of damaged DNA circulating in plasma containing high levels of 80HDG in combination with our urine and cell studies suggests that SLE patients cannot ef%iently remove 80HDG from cellular DNA which may result in cell death and release of oxidised DNA. In addition, we have previously shown that denaturation of double-stranded DNA by ROS results in an increased binding of anti-DNA antibodies present in sera from SLE patients [30] and that ROS modification of human DNA produces a more discriminating antigen for the diagnosis of SLE [36]. ROS-damaged DNA may, therefore, play a significant role in the generation of immune complexes which are of recognised importance in the pathogenesis of this disease.…”
Section: D~cu~ionmentioning
confidence: 99%
“…The presence of anti-DNA autoantibodies in the sera of SLE patients has long been considered as a marker of the disease as well as the pathogenic factor for its renal manifestations. It has been reported that denaturation of dsDNA by ROS results in an increased binding of anti-DNA antibodies present in the sera of SLE patients (33) and reactive oxygen species (ROS)-modified DNA is a better and more discriminating immunogen than native DNA (nDNA) for the production of anti-DNA autoantibodies in SLE (34). The detection of 8-hydroxydeoxyguanosine the DNA isolated from the serum of SLE patient (35) reinforces the evidence that ROS many be involved in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DNA after exposure to ROS presents a more discriminating antigen than native DNA for the binding of SLE autoantibodies [19,20]. Previously, we have shown that modification of double-stranded calf thymus DNA by ROS results in an increased binding of anti-DNA autoantibodies found in SLE sera [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ROS-DNA, approximately 0-2 ug/ml of antigen was required for a similar level of inhibition. Earlier studies have shown that DNA denatured by ROS served as a better antigen for antibodies found in SLE sera [19,20].…”
Section: Binding Specificity Of Sle Autoantibodiesmentioning
confidence: 99%